Karakter Fisik Dan Aktivitas Antibakteri Sabun Padat Ekstrak Kulit Pisang Mas (Musa Acuminata Colla) Terhadap Staphylococcus Aureus - Darsini; Desi Sri Rejeki; Endang Istriningsih; Setyo Wulandari, Prihastini (Journal of Chemistry Sciences and Education, 2025)
Solid soap is a type of skin cleanser formulation that functions to remove dirt, oil, and microorganisms such as bacteria. This study aims to formulate a solid bath soap containing ethanol extract of "pisang mas" banana peel (Musa acuminata) and to evaluate its antibacterial effectiveness against Staphylococcus aureus. The "pisang mas" banana peel was selected due to its content of active compounds such as flavonoids, saponins, and tannins, which are known to possess antibacterial properties. The extraction process was carried out by maceration using 96% ethanol, yielding an extract with a yield of 34.4%. The solid soap was formulated with four variations of extract concentrations: 0% (control), 8%, 10%, and 12%. Each formulation was subjected to physical quality tests including organoleptic properties, moisture content, foam height, and pH, in accordance with the Indonesian National Standard (SNI 06-3532-1994). Antibacterial activity was evaluated using the disc diffusion method against Staphylococcus aureus. The results demonstrated that all formulations met the quality standards for solid soap. The antibacterial test showed that extract concentrations of 8%, 10%, and 12% produced inhibition zones of 7.8 mm, 9 mm, and 16 mm, respectively, while the negative control showed an inhibition zone of 8.2 mm. These data indicate that increasing the concentration of "pisang mas" banana peel extract in the solid soap formulation positively correlates with enhanced antibacterial activity. The 12% concentration exhibited the strongest antibacterial effect. Therefore, ethanol extract of "pisang mas" banana peel shows potential as a natural active ingredient in antibacterial solid soap formulations.